Insight into MAPb1−xEuxI3 based perovskite solar cell performance using SCAPS Simulator - Bouri, Nabil; Talbi, Abdelali; Khaaissa, Yassine; Derbali, Sarah; Bouich, Amal; Nouneh, Khalid (Optik (Stuttgart), 2022)
The organic/inorganic Perovskite Solar Cells (PSC) are considered promising devices thanks to their higher efficiency, which made them a broad field of several studies, especially methylammonium lead iodide solar cells, However, the presence of lead, high toxicity, and low stability are the main obstacles in front of the commercialization of these devices. Herein, the one-dimensional SCAPS-1D numerical simulator model has been used to investigate the performance of PSC, using the Europium (Eu) instead of some Pb atoms to reduce undesirable effects, which give (MAPb1−xEuxI3) as absorber layer. Therefore, to enhance the performance parameters of the device and to achieve a higher power conversion efficiency (PCE) value compared to those existing in the literature, the study of the thickness effect and the active layer defects, using different Hole Transport Layer (HTL): NiOx,PEDOT:PSS,Spiro−OMeTAD,Cu2O was performed. In addition, the optimization of HTL parameters by varying the thickness and the concentration of the shallow acceptor was carried out. This Results show that the Cu2O as HTL with a thickness of 10 nm and concentration of the shallow acceptor of 1016 cm−3, combined with MAPb1−xEuxI3 active layers with a thickness of 289.5 nm and defect concentration of 1014 cm−3 gives the best PCE with a value of 21.72%. [Display omitted]